Steric Effects on Reaction Rates Correlation Analysis of Solvolysis Data for Tertiary Carbon Substrates - Paul Müller; Jacky Blanc; Jiri Mareda (CHIMIA)
Rate constants for solvolysis of tertiary chlorides and p-nitrobenzoates are compared and converted to Bentley’s unified reactivity scale. For the majority of structures consistent behavior is observed. Deviations are interpreted in terms of F-strain dr, to a minor extent, of leaving group hindrance. The reactivity of the tricyclic compound 31-OPNB can be rationalized by strain calculations if F-strain due to the presence of the OPNB substituent is taken into consideration.